2000
DOI: 10.1016/s0928-8244(00)00175-9
|View full text |Cite
|
Sign up to set email alerts
|

Roles of endogenous cytokines in liver apoptosis of mice in lethal Listeria monocytogenes infection

Abstract: Various bacterial pathogens have been identified as mediators of apoptosis. Apoptosis reportedly shows both detrimental and beneficial effects on biological functions. We studied the role of liver apoptosis in lethal Listeria monocytogenes infection and the regulation of apoptosis by endogenous cytokines during infection. Apoptosis was observed in the spleen but not in the liver of infected mice, whereas the induction of liver necrosis was evident by rising levels of serum aminotransferases in these animals. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 22 publications
0
15
0
1
Order By: Relevance
“…Apoptosis in response to infection with whole, viable L. monocytogenes has been described in hepatocytes [328][329][330], epithelial cells [128], CD4 + T cells, CD8 + T cells, and B lymphocytes [125,130,134], neurons, Purkinje cells [127], dendritic cells [124,331], and natural killer (NK) cells [129] but not in macrophages [8,124,332]. Whether intracellular Listeriae actively impede PCD in macrophages to preserve their intracellular niche is an interesting and unresolved question [333].…”
Section: Streptococcus Sppmentioning
confidence: 99%
See 1 more Smart Citation
“…Apoptosis in response to infection with whole, viable L. monocytogenes has been described in hepatocytes [328][329][330], epithelial cells [128], CD4 + T cells, CD8 + T cells, and B lymphocytes [125,130,134], neurons, Purkinje cells [127], dendritic cells [124,331], and natural killer (NK) cells [129] but not in macrophages [8,124,332]. Whether intracellular Listeriae actively impede PCD in macrophages to preserve their intracellular niche is an interesting and unresolved question [333].…”
Section: Streptococcus Sppmentioning
confidence: 99%
“…TNF-α appears to be crucial in directing a separate, CD8 + T-lymphocytemediated PCD pathway in hepatocytes in the absence of perforin and FAS [350]. Miura et al (2000), however, reported that TNF-α and IL-6 play a protective role in mediating survival of hepatocytes during listeriosis [329]. In support of this finding, pancreatic cells in mice lacking TRp55, a key receptor for TNF-α, are prone to PCD triggered by L. monocytogenes [351].…”
Section: Streptococcus Sppmentioning
confidence: 99%
“…In particular, the production of proinflammatory cytokines such as TNF-a and IFN-g and the recruitment of inflammatory monocytes to sites of infection are crucial for the early control of L. monocytogenes (32,33). Infection also leads to robust production of IL-6, and IL-6 deficiency or IL-6 neutralization with Abs results in enhanced susceptibility to L. monocytogenes (6,(34)(35)(36)(37)(38)(39)(40)(41); however, mechanisms of IL-6-mediated protection are so far unclear.…”
mentioning
confidence: 99%
“…Secretion of TNF-␣ has been shown to be critical for the resolution of a variety of bacterial, fungal, and parasitic infections. The absence of TNF-␣ bioactivity results in significant increases in mortality which correlate with an inability to clear the infectious agent (10,17,22,26,43,45,48). Conversely, excessive TNF-␣ production in the context of systemic bacterial infection, abdominal sepsis, or endotoxemia results in increased mortality and organ injury (20,21,36,46).…”
mentioning
confidence: 99%